Factors influencing fluctuation of Malaysian Ringgit / Muhammad Syazwi Awalludin - Awalludin, Muhammad Syazwi (Faculty of Business and Management, 2019)
The aim of this study is to identify the relationship between macroeconomic variables which are inflation, gross domestic product, crude oil price and export goods and services towards Malaysian Ringgit. The study used Multiple Linear Regression in order to find the relationship among the macroeconomic factors. The annually data collected for all the variables from the year 1987 until 2017. From the result, it reveals that only, crude oil price have a negative significant relationship towards Malaysia exchange rate while the export goods and services have a significant positive relationship. It means that crude oil price and exports goods and services influence the Malaysia exchange rate. From this study public will get the knowledge about the exchange rate will get clear idea in making decision.